Ben-Hur [videorecording (DVD)] - Wyler, William, 1902-1981; Zimbalist, Sam; Tunberg, Karl; Heston, Charlton; Hawkins, Jack, 1910-1973; Harareet, Haya, 1931-2021; Surtees, Robert; Boyd, Stephen, 1931-1977; Griffith, Hugh, 1912-1980; Scott, Martha, 1914-2003; O'Donnell, Cathy, 1925-1970; Jaffe, Sam, 1891-1984; et al. (Warner Home Video, 2011)
"Judah Ben-Hur [is] a Jewish nobleman in Palestine whose heroic odyssey includes enslavement by the Romans, vengeance against his tormentors during a furious arena chariot race and fateful encounters with Jesus Christ"--Container.